Drought vulnerability and impacts of climate change on livestock production and productivity in different agro-Ecological zones of Ethiopia. Issue 1 (31st December 2022) - Bogale, Girma Asefa; Erena, Zelalem Bekeko
ABSTRACT: Drought is a complicated natural hazard that has far-reaching social and environmental impacts. In Ethiopia's diverse agro ecological zones, drought remains a severe challenge and problem. Livestock rising is one of the agricultural sub-sectors that provide income and livelihood to around one-third of African inhabitants and accounts for 30–50 percent of agricultural GDP. Pastoralists on the Ethiopia-Kenya-Somalia border endured extreme suffering, including the loss of nearly 80% of their cattle and huge migration out of drought-stricken areas. Drought can cause severe economic hardship and stress for farmers and local economies, like; lost productivity, population reduction, and the trauma of witnessing livestock, crops, soil, and native vegetation damage. Between 1990 and 2000, and 2001-2002/03, drought-related animal death rates in the Somali region increased by 60% and 80% of the entire cattle population, respectively. Drought has the greatest immediate effects on farmers, including depletion of water resources, crop failure, and an increase in food prices, ill health, livestock output losses and death, and a decline in livestock prices in the Borana zone. Drought adaptation and mitigation measures depending on geography and livestock system may improve the study's trajectory in the future if further review is done.